End-to-side "loop" graft for total facial nerve reconstruction: Over 10 years experience. Issue 8 (August 2015) - Matsuda, Ken; Kakibuchi, Masao; Sotsuka, Yohei; Kubo, Tateki; Shibata, Minoru; Hosokawa, Ko
Summary: Background: Multiple-branch reconstruction is required in order to attain facial reanimation for extensive facial nerve defects. We previously reported that end-to-side nerve grafting, with the use of a single nerve graft for defect reconstruction, was easy to perform. We have also demonstrated the efficacy of end-to-side nerve suture of the recipient nerve to the donor graft nerve, in experimental rat models and clinical cases. The regenerating axons, which extended into the nerve graft, were "distributed" to multiple recipient nerves via end-to-side nerve-suture sites. Methods: Thirty-two patients who underwent facial nerve reconstruction (five to 10 branches) had a single sural nerve graft coapted to the proximal stump of the facial nerve in an end-to-end manner, followed by end-to-side nerve suture of the recipient nerve stumps to the side of the nerve graft. In 19 patients who were expected to undergo postoperative radiotherapy and/or chemotherapy, the distal end of the graft was connected to the side of the hypoglossal nerve for "axonal supercharging, " to enhance the recovery of the facial muscles. Results: Initial facial movements were noted at 5–12 months postoperatively, and good recovery (House–Brackmann grade III/IV) was observed during long-term follow-up in most patients. Conclusion: End-to-side nerve suture of the recipient nerve stumps to the nerve graft requires less graft nerve material and less technical mastery to reconstruct multiple branches of the facial nerve. We also described the concept of "axonal supercharging, " namely the connection of double-donor neural sources to the graft, and "axonal distribution, " namely the reinnervation of multiple recipient nerve stumps connected to the graft in an end-to-side manner. This combination of axonal supercharging and distribution can be a useful option in facial nerve reconstruction.